Migracións de Rafa Villar. Unha análise temática - Lamela Rodríguez, Olalla (Madrygal. Revista de Estudios Gallegos, 2010)
This is a brief guide to the thematic lines that can be found in the collection of poems Migracións, by Rafa Villar. There are four nuclei standing out: migrations, historical memory, intimism and meta-literature. They link together. These compositions are united by bonds among them, in a melodic way, and the overall result is that of a whole.